0095 The Effect of Chronic Intermittent Hypoxia (CIH) on Spatial Learning in Rats. (27th April 2018) - Azad, N; Brake, L A; Keenan, B T; Leinwand, S E; Wiemken, A S; Nguyen, T T; Lin, T C; Schwab, R J
Abstract: Introduction: Patients with Obstructive Sleep Apnea (OSA) commonly manifest cognitive impairment and neurodegeneration that may be due to hypoxic damage during sleep. This study investigated the effects of intermittent hypoxia on spatial learning in a rat model using a Barnes maze paradigm. We hypothesized that spatial learning would be increasingly impaired as a function of hypoxia severity. Methods: Twenty-one male Sprague-Dawley rats were split into three hypoxia conditions: severe (6% oxygen; n=7), moderate (11% oxygen; n=5), and sham (21% oxygen; n=9). Rats were exposed to hypoxic conditions (180 second periods of cyclical oxygen between 21% and condition-specific nadir O2 ) for 12 hours during the day in enclosed housing chambers designed to output appropriate air compositions. Barnes maze testing was performed monthly. Rats were placed on a platform containing 19 shallow holes with a single "target box" to escape the maze. At each month, rats had 3 minutes to find the "target box" during four daily trials over four consecutive days. Maze completion time and number of errors were recorded. Results: Rats from the three hypoxia groups did not differ in metrics of spatial learning at baseline. By month 3, the sham group showed a faster improvement in maze completion time across four days compared to both moderate (p=0.0071) and severe (p=0.0281) groups. Within the severe hypoxia group, maze completion time was significantly longer at month 3 compared to baseline on day 2 (p=0.0057), day 3 (p=0.0023) and day 4 (p=0.0336). Similarly, the sham group showed a quicker improvement in number of errors made across four days compared to the severe group at month 3 (p=0.0087). Conclusion: Our findings indicate that spatial learning, measured by shorter completion times and fewer errors, is impaired in rats undergoing 3 months of cyclical intermittent hypoxia when compared to sham animals. Results add to the growing body of evidence on the relationship between obstructive sleep apnea and cognitive impairment. Support (If Any): Funded by NIH P01 HL094307.